Visit of Prime Minister Dr. Manmohan Singh to Brazil and Cuba, September 10-18, 2006 [First IBSA Summit & XIV NAM Summit]. - Manmohan Singh 1932- (Public Diplomacy Division, Ministry of External Affairs, Government of India, 2006)
Addresses of Indian prime minister on diplomatic and trade relations delivered during his visit to Brazil and Cuba; includes his addresses at First IBSA Summit & XIV NAM Summit.